A soy‐based jerky made from transglutaminase‐treated yuba film. Issue 12 (2nd October 2022) - Jin, Ye; Song, Ka‐Young; Kim, Yookyung
Abstract: Yuba film was used as plant‐based jerky. To increase the cross‐linking of soy proteins, yuba films (Y) were treated with transglutaminase (TG) at different temperatures: 45°C (YT45), 50°C (YT50), and 55°C (YT55). FTIR confirmed the strongest cross‐linking effect of TG at 1632 and 1529 cm −1 in YT55 compared to YT45 and YT50. The free‐SH decreased with increasing temperature, whereas the ‐S‐S‐ cross‐linking increased in TG‐treated yuba jerky (YTs). The YT showed improved texture, cutting stress, and cohesiveness. The hardness of YTs was higher than that of Y (14.64 N). SEM showed that with increasing temperature, yuba jerky developed a smoother surface with a compact and denser network. Yuba jerky had high isoflavone and flavonoid. The aw of yuba jerky was between 0.861 and 0.886 during 6 days of storage at 25°C. Thus, YT has the potential to be used as a meat analog with good nutrients and shelf life. Novelty impact statement: This study used yuba film to develop a beef jerky analog. To improve the adhesiveness of the Yuba layer via the cross‐linking of soy protein, TG treatment was applied at different temperatures prior to vacuum packaging. Our results demonstrated that yuba jerky could be a potential choice as a meat analog with a softer texture and lower cutting stress and with similar chewiness to beef jerky by using TGase to improve cross‐linking of plant‐based proteins.